Extração de proteínas e carboidratos da biomassa de Spirulina platensis e caracterização da fração proteica - Lupatini, Anne Luize (2016)
Spirulina platensis is considered an unconventional source of protein, because its avorably constitution on this component (46 to 63%), which is higher than the meat and soy. Furthermore, it has potential as a feedstock for bioethanol production and can accumulate between 8.0 to 14.0% of carbohydrate. In order to cover the concept of Integrated Biorefineries, the aim of this study was to evaluate the combined extraction of proteins and carbohydrates from Spirulina platensis biomass using sonication and agitation, under alkaline conditions, and the subsequent production and characterization of protein concentrate. The first stage of this work consisted of applying a sequential strategy of experimental design (Fractional Factorial Design FFD) and Central Composite Rotatable Design (CCRD)) by selecting and maximizing variables with significant influence on the protein and carbohydrates extraction. With the extraction conditions established, a final yield of 75.85% and 41.54% from protein and carbohydrate, respectively, was reached. In the second step, the protein concentrate obtained by precipitation was submitted to chemical and echnological functionality analyzes. The protein concentrate showed blue-green color with 75.97% of proteins (dry weight), appreciable concentrations of amino acids, where tryptophan had the highest chemical score (1.71) and the limiting amino acid was histidine; the secondary structure of proteins showed that the most abundant conformations present were β-sheet and α-helice. At the step of echnological functionality evaluation it was observed that the pH influenced on the properties of water absorption capacity, foaming and emulsion capacity and stability, and gelation capacity; it can be justified by the solubility of this protein which is minimal at pH 3.0 and maximum at 9.0. The level of addition of protein concentrate also interfered on the performance of these properties; better results have been obtained at higher concentrations levels, except for water and oil absorption capacity. Thus, it was confirmed that the Spirulina platensis proteins may contribute in different ormulations of foods, having effective characteristics to form emulsions, foams or gels, and can be used as a supplemental source of protein.